History of Inundation in Northern Bihar - Paswan, Madan (Recent Research in Science and Technology, 2011)
India is a land of various natural and cultural diversities where natural calamities like floods, storms, earth quack, land slides are very natural occurrences. The problem of Inundation (floods) that has caused thousands of human lives occurs when a gently flowing river suddenly gets overflowed of their edges during Monsoon. The demonic flow of the huge stream has devastated the entire Northern Bihar which has always been its victim over the years. This paper is a micro yet analytical scrutiny of the problem of Inundation in the Northern Bihar in particular touching it with historical perspective.